Diagnosis and Management of Acute Benign Anorectal Disease: ROUND TABLE - Almeida, Isabel; Viola Malet, Marcelo; Olivera, Eduardo; Curi, Jorge; Saya, Ana; Estapé (h), Gonzalo; Genta, Sandra; Borgno, Laura; Soler, Anahí; Vázquez, Aníbal (Cirugía del Uruguay, 2000)
It is a topic that is of great interest for most surgeons, especially for those in formation. The diseases that cover this topic have varied clinical presentations, which makes it difficult your diagnosis; because there is no uniformity criteria in the treatment, we will carry out this presentation to understand the disease and guide diagnostic and therapeutic behaviors.